2021
DOI: 10.1021/acs.chemmater.0c03852
|View full text |Cite
|
Sign up to set email alerts
|

Ferrite Materials Containing Kagomé Layers: Chemistry of Ba2Fe11Ge2O22 and K2Co4V9O22 Hexaferrites

Abstract: Hexaferrites have a wide range of technological applications as well as a rich and complicated structural chemistry, with iron oxide layers inducing highly anisotropic ferrimagnetism that remains intact to high temperatures (>400 K). Most hexaferrites (i.e., M-type BaFe12O19) contain the dominant magnetic vectors normal to the hexagonal planes forming hard ferrimagnets, while the much less common Y-type investigated here typically contains the ferrimagnetic vectors in the iron oxide planes, creating soft ferri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 67 publications
1
0
0
Order By: Relevance
“…We were also curious if the vesuvianite structure type could be expanded into a new phase space through the substitution of the larger tetrahedral Ge 4+ ion for Si 4+ . We have recently been examining the role of germanate as a building block in transition metal oxides and have observed some complex structural chemistry [23,24]. In the present case, we found that the larger germanate can accommodate the larger Fe 3+ ion in the trivalent Al 3+ sites, as well as the larger Sr 2+ ion in the Ca 2+ sites.…”
Section: Introductionsupporting
confidence: 52%
“…We were also curious if the vesuvianite structure type could be expanded into a new phase space through the substitution of the larger tetrahedral Ge 4+ ion for Si 4+ . We have recently been examining the role of germanate as a building block in transition metal oxides and have observed some complex structural chemistry [23,24]. In the present case, we found that the larger germanate can accommodate the larger Fe 3+ ion in the trivalent Al 3+ sites, as well as the larger Sr 2+ ion in the Ca 2+ sites.…”
Section: Introductionsupporting
confidence: 52%